A sodium ion battery layered positive electrode material and preparation method thereof

By coating NaFePO4 and Na3FePO4CO3 on the positive electrode material of sodium ion battery, the problems of high residual alkali on the surface of the material and poor air stability are solved, and the effect of reducing residual alkali content and improving cycle stability is achieved.

CN118919710BActive Publication Date: 2025-03-11HENAN KELONG NEW ENERGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411411809.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-03-11
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

The O3-phase layered positive electrode material of sodium ion battery has poor chemical stability in the air and has a high residual alkali content on the surface, which leads to particle agglomeration and slurry gel during electrode preparation, hindering the actual feasibility of the material.

Method used

NaFePO4 and Na3FePO4CO3 are used as surface cladding layers, and NaFePO4CO3 is used to react FeC2O4·H2O and (NH4)2HPO4 with the residual alkali on the surface of the positive electrode material, and then mixed with acetylene black to form a Na3FePO4CO3 cladding layer, which consumes residual alkali on the surface of the material twice, reduces the residual alkali content and improves material stability.

Benefits of technology

It effectively reduces the residual alkali content on the surface of the positive electrode material of the sodium ion battery, improves the air stability and slurry stability of the material, reduces the gas production during the circulation, and improves the circulation stability performance of the sodium ion battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118919710B_ABST
    Figure CN118919710B_ABST
Patent Text Reader

Abstract

The invention discloses a sodium ion battery layered positive electrode material and a preparation method thereof. First, FeC2O4·H2O and (NH4)2HPO4 react with residual alkali sodium carbonate on the surface of the positive electrode material to generate a NaFePO4 coating layer. Secondly, the generated NaFePO4 coating layer reacts with the added acetylene black and further reacts with the surface sodium carbonate to generate Na3FePO4C03. By consuming the residual alkali sodium carbonate on the surface of the material twice, the residual alkali on the surface of the positive electrode material can be effectively reduced, and the stability of the material in the air can be effectively improved; and the slurry stability of the positive electrode material can be improved, and the gas generation after the sodium ion battery cycle process can be reduced. The coating layer formed by the positive electrode material of the sodium ion battery can be isolated from the electrolyte, reducing the direct contact between the positive electrode of the sodium ion battery and the electrolyte, and ensuring the stability of the interface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion battery positive electrode materials, and in particular relates to a sodium ion battery layered positive electrode material and a preparation method thereof. Background Art

[0002] The urgency of developing clean energy technologies has led to extensive research into high-energy, low-cost electrical energy storage devices for large-scale grid storage. From a cost and sustainability perspective, the use of sodium-ion batteries is more attractive than lithium-ion batteries because they are more abundant and less expensive than lithium-ion batteries.

[0003] The prospect of O3-phase layered materials for sodium-ion batteries is challenging due to their poor chemical stability to air and high residual alkali content on the surface. This high residual alkali content triggers defluorination of the polyvinylidene fluoride (PVDF) binder during cathode preparation, leading to particle agglomeration and slurry gelation during electrode preparation, greatly hindering the practical feasibility of O3-phase layered cathode materials.

[0004] Related research on reducing the residual alkali content on the surface of materials has been reported. For example, patent document CN 111370664A discloses that a volatile acidic gas is introduced into an atmosphere rotary furnace for 1-5 hours to remove the residual alkali on the surface of a layered positive electrode material for a sodium ion battery. After cooling to room temperature, the layered positive electrode material with reduced surface residual alkali is obtained. While this method significantly reduces the residual alkali content and pH of the layered positive electrode material, it is not suitable for large-scale production due to its high equipment requirements.

[0005] For example, patent document CN 116613294A discloses a method for preparing a sodium-ion battery by sintering and mixing two precursors of different particle sizes, and then controlling sintering and coating conditions to achieve an excellent crystal structure. This method produces a sodium-ion battery with a specific XRD crystal structure, which improves the surface stability of the cathode material, prevents side reactions with the electrolyte and metal ion dissolution, and reduces the residual alkali content of the cathode material. While this specific XRD crystal structure reduces the residual alkali content of the cathode material, it is difficult to control.

[0006] For example, patent document CN 117466346A discloses a sodium-ion battery cathode material, a preparation method thereof, and a sodium-ion battery. The preparation method comprises the following steps: weighing a nickel-manganese-iron hydroxide sodium precursor, a sodium source, and an additive and mixing them at high speed; subjecting the mixed materials to a primary high-temperature sintering; adding a first coating material, oxalic acid; subjecting the powder to high-speed mixing; and adding a second coating material and a third coating material to the powder after standing. The second coating material is a metal salt additive including any one or a combination of nickel carbonate, nickel oxalate, and ferrous oxalate; and the third coating material is a metal oxide additive including any one or a combination of titanium dioxide, tungsten trioxide, and molybdenum trioxide. After high-speed mixing, the materials are subjected to a secondary high-temperature sintering to obtain the desired sodium-ion battery cathode material. The preparation method comprises the following steps: during the primary sintering and secondary sintering processes, the first coating material is oxalic acid, which is used for acidolysis of residual alkali in the mixing stage, thereby improving the reaction activity and making it easier to combine with other coating metal elements, thereby reducing the residual alkali sodium ions in the system; the second coating material is used for rapid reaction with the residual alkali in the reaction system to generate a corresponding sodium-rich sodium-electric material, thereby increasing the capacity of the positive electrode material; the third coating material is used to improve the surface conductivity of the positive electrode material and increase the thickness of the coating layer of the positive electrode material; and the first coating material, the second coating material and the third coating material are used for secondary coating to achieve low residual alkali, reduced side reactions and thus reduced gas production, thereby improving cycle performance and enhancing its comprehensive performance, thereby providing a sodium ion battery positive electrode material and a sodium ion battery with low residual alkali, increased coating layer thickness, good coating layer conductivity, low gas production, and better capacity and cycle performance. In the process of reducing the residual alkali on the surface of the positive electrode material of the sodium ion battery, this method achieves the goal of reducing the residual alkali on the surface of the positive electrode material of the sodium ion battery while generating a corresponding sodium-rich structure of the sodium-ion battery material by sequentially adding oxalic acid and a metal additive in steps, thereby improving the capacity and cycle performance of the sodium ion battery. However, the optimal reduction in residual alkali content in the embodiment is 4600 ppm, or 0.46%. Therefore, the effect of reducing the residual alkali on the surface of the positive electrode material of the sodium ion battery by simply reacting the metal salt additive with the residual alkali produced by acid hydrolysis of oxalic acid to form the corresponding sodium-rich structure still needs to be further improved. Summary of the Invention

[0007] The technical problem solved by the present invention is to provide a sodium ion battery layered positive electrode material and a preparation method thereof. The sodium ion battery positive electrode material prepared by the method has excellent air stability, low residual alkali content, stable material processing performance, and the sodium ion battery prepared by the method has excellent cycle stability performance at high voltage.

[0008] The present invention adopts the following technical solution to solve the above technical problems. A layered cathode material for a sodium-ion battery is composed of a surface coating layer and an O3-type sodium-ion battery cathode material. The surface coating layer is NaFePO4 and Na3FePO4C03, and the O3-type sodium-ion battery cathode material is Na x Ni a Mn b Fe c Cu d M (1-a-b-c-d) O2, where 0.8 < x < 1.2, 0.1 < a < 0.7, 0.1 < b < 0.7, 0.1 < c < 0.7, 0.1 ≤ d ≤ 0.7, and M is one or more of Mg, Al, Ti, Co, Zn, Y or Zr.

[0009] The preparation method of the layered cathode material for a sodium-ion battery according to the present invention specifically comprises the following preparation steps:

[0010] Step S1, mixing a solution containing soluble nickel salt, soluble ferrous salt, soluble manganese salt and soluble copper salt to carry out a coprecipitation reaction to obtain a quaternary precursor material;

[0011] Step S2, mixing the quaternary precursor material obtained in Step S1 with a sodium source and a compound containing M, and then subjecting the mixture to high-temperature sintering to obtain a sodium-ion battery cathode material;

[0012] Step S3, mixing the sodium-ion battery cathode material obtained in Step S2 with FeC2O4·H2O and (NH4)2HPO4, and then using a wet planetary ball mill to mix evenly. During the mixing process, FeC2O4·H2O and (NH4)2HPO4 react with the residual alkali on the surface of the sodium-ion battery cathode material to generate NaFePO4. Then, the mixture is dried and ground, and then the obtained mixture is subjected to high-temperature sintering and pulverization to obtain a sodium-ion battery cathode material coated with NaFePO4;

[0013] Step S4, mixing the sodium-ion battery cathode material coated with NaFePO4 obtained in Step S3 with acetylene black, and then using a wet planetary ball mill to mix evenly under an inert gas atmosphere. During the mixing process, NaFePO4 coated on the surface of the sodium-ion battery cathode material coated with NaFePO4 and the residual alkali remaining on the surface react to generate Na3FePO4CO3, thereby obtaining a layered cathode material for a sodium-ion battery coated with NaFePO4 and Na3FePO4CO3

[0014] Furthermore, in step S1, the soluble nickel salt is one or more of nickel sulfate, nickel chloride or nickel nitrate; the soluble ferrous salt is one or more of ferrous sulfate, ferrous chloride or ferrous nitrate; the soluble manganese salt is one or more of manganese sulfate, manganese chloride or manganese nitrate; the soluble copper salt is one or more of copper sulfate, copper chloride or copper nitrate; the ratio of the soluble nickel salt, the soluble ferrous salt, the soluble manganese salt and the soluble copper salt satisfies Na x Ni a Mn b Fe c Cu d M (1-a-b-c-d) O2 stoichiometric coefficient ratio.

[0015] Furthermore, the sodium source in step S2 is one or more of sodium carbonate, sodium formate, sodium hydroxide, sodium acetate, sodium chloride or sodium fluoride, and the molar ratio of the sodium source to the quaternary precursor material satisfies Na / (Ni+Fe+Cu+Mn)=1:1; the compound containing M is an oxide or hydroxide containing M, wherein the oxide containing M is MgO, TiO2, Al2O3, ZnO, CoO, ZrO or Y2O3; the mass ratio of the compound containing M to the quaternary precursor material satisfies that the compound containing M is 0.08wt%~0.12wt% of the mass of the quaternary precursor material.

[0016] Furthermore, the specific process of high temperature sintering in step S2 is: first heating the mixture to 400-600°C in an air atmosphere and sintering for 4-8 hours, then heating it to 950-1050°C and sintering for 10-15 hours, with a heating rate of 2-5°C / min.

[0017] Furthermore, the feeding ratio of the sodium ion battery positive electrode material to FeC2O4·H2O and (NH4)2HPO4 in step S3 satisfies the molar ratio of the residual alkali content on the surface of the sodium ion battery positive electrode material to FeC2O4·H2O and (NH4)2HPO4 of 1:1~2:1~2.

[0018] Furthermore, the specific process of the ball milling mixing in step S3 is: ball milling at a rotation speed of 500-600 rpm for 1-2 hours.

[0019] Furthermore, the specific process of the high temperature sintering in step S3 is: heating the mixture to 600-700° C. in an inert gas atmosphere and annealing for 8-10 hours, with a heating rate of 2-5° C. / min.

[0020] Furthermore, the specific process of the ball milling mixing in step S4 is: first, ball milling at a rotation speed of 500~600 rpm for 5~6h, during which the amount of acetylene black added is 20wt%~30wt% of the mass of the NaFePO4-coated sodium ion battery positive electrode material coated NaFePO4; then ball milling at a rotation speed of 300~400 rpm for 3~4h, during which the amount of acetylene black added is 20wt%~30wt% of the mass of the NaFePO4-coated sodium ion battery positive electrode material coated NaFePO4.

[0021] Compared with the prior art, the present invention has the following advantages and beneficial effects: the sodium ion battery layered oxide positive electrode material provided by the present invention first reacts FeC2O4·H2O and (NH4)2HPO4 with the residual alkali sodium carbonate on the surface of the positive electrode material to generate a NaFePO4 coating layer, and then the generated NaFePO4 coating layer reacts with the added acetylene black and further reacts with the surface sodium carbonate to generate Na3FePO4CO3. By consuming the residual alkali sodium carbonate on the surface of the material twice, the residual alkali on the surface of the positive electrode material can be effectively reduced, and the stability of the material in the air can be effectively improved; and the slurry stability of the positive electrode material can be improved, and the gas production during the cycle of the sodium ion battery can be reduced. The coating layer formed by the positive electrode material of the sodium ion battery can be isolated from the electrolyte, reducing the direct contact between the positive electrode of the sodium ion battery and the electrolyte, and ensuring the stability of the interface. In addition, the positive electrode material coating layer is a sodium-containing compound, which can provide a part of the sodium source during the charge and discharge process of the sodium ion battery, further improving the cycle stability of the positive electrode material of the sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 2 are scanning electron microscope images of the positive electrode materials in Example 1 and Comparative Example 1.

[0023] Figure 2 This is the XRD pattern of the positive electrode material in Example 1.

[0024] Figure 3 This is the formation curve of the positive electrode material in Example 1.

[0025] Figure 4 These are the cycle test curves of the positive electrode materials in Examples 1-2 and Comparative Examples 1-2. DETAILED DESCRIPTION

[0026] The above contents of the present invention are further described in detail below through examples, but this should not be understood as limiting the scope of the above subject matter of the present invention to the following examples. All technologies implemented based on the above contents of the present invention fall within the scope of the present invention. Example

[0027] Step S1: Mix the salt solution containing Ni, Fe, Mn and Cu in the stoichiometric ratio to perform co-precipitation reaction to obtain the quaternary precursor material Ni 0.33 Mn 0.40 Fe 0.2 Cu 0.07 (OH)2.

[0028] Step S2: Sodium carbonate and the quaternary precursor material are added to a ball mill in a molar ratio of Na / (Ni+Fe+Cu+Mn)=1:1, and then MgO (0.1wt% of the mass of the quaternary precursor material) is added to the ball mill for mixing. After mixing evenly, a mixture is obtained. The mixture is first heated to 500°C in an air atmosphere and sintered for 6h, and then heated to 980°C and sintered for 12h, with a heating rate of 3°C / min, to finally obtain Mg-doped NaNi 0.33 Mn 0.40 Fe 0.2 Cu 0.07 O2 positive electrode material.

[0029] Step S3: Measure Mg-doped NaNi 0.33 Mn 0.40 Fe 0.2 Cu 0.07 The Na2CO3 content on the surface of the O2 positive electrode material is 12740ppm. According to the content of sodium carbonate on the surface of the positive electrode material, it is mixed with FeC2O4·H2O and (NH4)2HPO4 at a fixed molar ratio of 1:2:2. The mixture is ball milled at a speed of 600rpm for 1h using a wet planetary ball milling method, and then the mixture is dried and ground. The mixture is then heated to 600℃ at a heating rate of 5℃ / min under an argon atmosphere and annealed for 8h to obtain a NaFePO4-coated sodium ion battery positive electrode material.

[0030] Step S4: ball-milling the NaFePO4-coated sodium ion battery positive electrode material and acetylene black. The ball milling mixing process is divided into two steps: first, ball milling at a speed of 500 rpm for 6 hours. During this process, the amount of acetylene black added is 25wt% of the mass of the NaFePO4-coated sodium ion battery positive electrode material coated with NaFePO4; then ball milling at a speed of 400 rpm for 4 hours. During this process, the amount of acetylene black added is 25wt% of the mass of the NaFePO4-coated sodium ion battery positive electrode material coated with NaFePO4. The entire ball milling process is carried out in an argon-filled container to finally obtain a sodium ion battery layered positive electrode material coated with NaFePO4 and Na3FePO4CO3.

[0031] The morphology of the cathode material was tested by field emission scanning electron microscopy. The test results are shown in Figure 1 The residual alkali of the cathode material was tested by titration method. The test results are shown in Table 1.

[0032] The prepared NaFePO4 and Na3FePO4CO3 coated sodium ion battery layered cathode materials were prepared into CR2032 button cells, which were conventionally formed with a formation voltage of 2.0~4.2V and a formation rate of 0.2C. The formation curve is shown in Fig. Figure 3 The rate performance test of the sodium ion battery after formation is carried out, and the results are shown in Table 2. The cycle performance test of the battery after formation is carried out under the conditions of constant temperature of 23℃, 0.5C charging and 1C discharging, and the step is set to cycle 100 weeks to record the capacity retention rate. The results are shown in Figure 4 . Example

[0033] Step S1: Mix the salt solution containing Ni, Fe, Mn and Cu in the stoichiometric ratio to perform co-precipitation reaction to obtain the quaternary precursor material Ni 0.33 Mn 0.40 Fe 0.2 Cu 0.07 (OH)2.

[0034] Step S2: Sodium carbonate and the quaternary precursor material are added into a ball mill in a molar ratio of Na / (Ni+Fe+Cu+Mn)=1:1, and then 0.1wt% of the mass of the quaternary precursor material TiO2 is added into the ball mill for mixing. After mixing evenly, a mixture is obtained. The mixture is first heated to 500°C in an air atmosphere and sintered for 6h, and then heated to 980°C and sintered for 12h, with a heating rate of 3°C / min, to finally obtain Ti-doped NaNi 0.33 Mn 0.40 Fe 0.2 Cu 0.07 O2 positive electrode material.

[0035] Step S3: Measure Ti-doped NaNi 0.33 Mn 0.40 Fe 0.2 Cu 0.07 The Na2CO3 content on the surface of the O2 positive electrode material is 12603ppm. According to the content of sodium carbonate on the surface of the positive electrode material, it is mixed with FeC2O4·H2O and (NH4)2HPO4 at a fixed molar ratio of 1:2:2. The mixture is ball milled at a speed of 600rpm for 1h using a wet planetary ball milling method, and then the mixture is dried and ground. The mixture is then heated to 600℃ at a heating rate of 5℃ / min under an argon atmosphere and annealed for 8h to obtain a NaFePO4-coated sodium ion battery positive electrode material.

[0036] Step S4: ball-milling the NaFePO4-coated sodium ion battery positive electrode material and acetylene black. The ball milling mixing process is divided into two steps: first, ball milling at a speed of 500 rpm for 6 hours. During this process, the amount of acetylene black added is 25wt% of the mass of the NaFePO4-coated sodium ion battery positive electrode material coated with NaFePO4; then ball milling at a speed of 400 rpm for 4 hours. During this process, the amount of acetylene black added is 25wt% of the mass of the NaFePO4-coated sodium ion battery positive electrode material coated with NaFePO4. The entire ball milling process is carried out in an argon-filled container to finally obtain a sodium ion battery layered positive electrode material coated with NaFePO4 and Na3FePO4CO3.

[0037] The prepared NaFePO4 and Na3FePO4CO3 coated sodium ion battery layered positive electrode materials were prepared into CR2032 button batteries, which were subjected to conventional formation with a formation voltage of 2.0~4.2V and a formation rate of 0.2C. The rate performance of the formed sodium ion battery was tested, and the results are shown in Table 2. The cycle performance of the formed battery was tested under the conditions of a constant temperature of 23℃, 0.5C charging and 1C discharging, and the process step was set to 100 cycles to record the capacity retention rate. The results are shown in Table 2. Figure 4 .

[0038] Comparative Example 1

[0039] Step S1: Mix the salt solution containing Ni, Fe, Mn and Cu in the stoichiometric ratio to perform co-precipitation reaction to obtain the quaternary precursor material Ni 0.33 Mn 0.40 Fe 0.2 Cu 0.07 (OH)2.

[0040] Step S2: Sodium carbonate and the quaternary precursor material are added to a ball mill in a molar ratio of Na / (Ni+Fe+Cu+Mn)=1:1, and then MgO (0.1wt% of the mass of the quaternary precursor material) is added to the ball mill for mixing. After mixing evenly, a mixture is obtained. The mixture is first heated to 500°C in an air atmosphere and sintered for 6h, and then heated to 980°C and sintered for 12h, with a heating rate of 3°C / min, to finally obtain Mg-doped NaNi 0.33 Mn 0.40 Fe 0.2 Cu 0.07 O2 positive electrode material.

[0041] The prepared Mg-doped NaNi 0.33 Mn 0.40 Fe 0.2 Cu 0.07The O2 positive electrode material was prepared into a CR2032 button cell, which was subjected to conventional formation with a formation voltage of 2.0~4.2V and a formation rate of 0.2C. The rate performance test of the formed sodium ion battery was performed, and the results are shown in Table 2. The cycle performance test of the formed sodium ion battery was performed under the conditions of a constant temperature of 23℃, 0.5C charging and 1C discharging, and the process step was set to 100 cycles to record the capacity retention rate. The results are shown in Table 2. Figure 4 .

[0042] Comparative Example 2

[0043] Step S1: Mix the salt solution containing Ni, Fe, Mn and Cu in the stoichiometric ratio to perform co-precipitation reaction to obtain the quaternary precursor material Ni 0.33 Mn 0.40 Fe 0.2 Cu 0.07 (OH)2.

[0044] Step S2: Sodium carbonate and the quaternary precursor material are added to a ball mill in a molar ratio of Na / (Ni+Fe+Cu+Mn)=1:1, and then MgO (0.1wt% of the mass of the quaternary precursor material) is added to the ball mill for mixing. After mixing evenly, a mixture is obtained. The mixture is first heated to 500°C in an air atmosphere and sintered for 6h, and then heated to 980°C and sintered for 12h, with a heating rate of 3°C / min, to finally obtain Mg-doped NaNi 0.33 Mn 0.40 Fe 0.2 Cu 0.07 O2 cathode material.

[0045] Step S3: Measure Mg-doped NaNi 0.33 Mn 0.40 Fe 0.2 Cu 0.07 The Na2CO3 content on the surface of the O2 positive electrode material is 12740ppm. According to the content of sodium carbonate on the surface of the positive electrode material, it is mixed with FeC2O4·H2O and (NH4)2HPO4 at a fixed molar ratio of 1:2:2. The mixture is ball milled at a speed of 600rpm for 1h using a wet planetary ball milling method, and then the mixture is dried and ground. The mixture is then heated to 600℃ at a heating rate of 5℃ / min under an argon atmosphere and annealed for 8h to obtain a NaFePO4-coated sodium ion battery positive electrode material.

[0046] The prepared NaFePO4-coated sodium ion battery cathode material was prepared into a CR2032 button cell and subjected to conventional formation with a formation voltage of 2.0-4.2V and a formation rate of 0.2C. The rate performance test of the formed battery was conducted, and the results are shown in Table 2. The cycle performance test of the formed battery was conducted at a constant temperature of 23°C, with a charge of 0.5C and a discharge of 1C. The process step was set to cycle 100 cycles and the capacity retention rate was recorded. The results are shown in Table 2. Figure 4 .

[0047] Table 1

[0048]

[0049] Table 2

[0050]

[0051] From Table 1, by comparing the residual alkali content of the positive electrode materials of Examples 1-2 and Comparative Examples 1-2, it can be found that after two consumptions of sodium carbonate, the sodium carbonate content on the surface of the positive electrode material is significantly reduced. At the same time, the sodium hydroxide content on the surface of the positive electrode material is also significantly reduced, indicating that this method can effectively reduce the residual alkali on the surface of the positive electrode material of the sodium ion battery and thus improve the processing performance of the positive electrode material.

[0052] From Table 2, by comparing the capacity and rate performance of the positive electrode materials prepared in Examples 1-2 and Comparative Examples 1-2, it can be found that coating NaFePO4 and Na3FePO4C03 on the sodium ion battery positive electrode material does not affect the capacity and rate performance of the sodium ion battery positive electrode material.

[0053] from Figure 1 It can be clearly seen from the scanning electron microscope (SEM) image provided in the figure that the surface of the sample prepared in Example 1 is covered with a layer of material, while the surface of the sample prepared in Comparative Example 1 is relatively smooth.

[0054] from Figure 2 The X-ray diffraction pattern provided in can confirm that the sodium ion battery positive electrode material prepared by this embodiment still retains the O3 phase layered transition metal oxide.

[0055] Figure 4 It is the cycle capacity retention rate of the sodium ion battery assembled with the sodium ion ground pool positive electrode materials prepared in Examples 1~2 and Comparative Examples 1~2. It can be seen from the figure that compared with Comparative Examples 1~2, the sodium ion battery positive electrode material prepared in Examples 1~2 has excellent cycle stability performance.

[0056] The above embodiments describe the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the scope of the principles of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of protection of the present invention.

Claims

1. A method for preparing a layered positive electrode material for a sodium ion battery, characterized in that: The layered cathode material of the sodium-ion battery is composed of a surface coating layer and an O3-type sodium-ion battery cathode material. The surface coating layer includes NaFePO4 and Na3FePO4CO3. The O3-type sodium-ion battery cathode material is Na d , (1-a-b-c-d) , b , c , a Ni a Mn b Fe c Cu d M (1-a-b-c-d) O2, where 0.8 < x < 1.2, 0.1 < a < 0.7, 0.1 < b < 0.7, 0.1 < c < 0.7, 0.1 ≤ d ≤ 0.7, and M is one or more of Mg, Al, Ti, Co, Zn, Y, or Zr; The specific preparation steps of the sodium ion battery layered positive electrode material are: Step S1, mixing solutions containing a soluble nickel salt, a soluble ferrous salt, a soluble manganese salt and a soluble copper salt to perform a coprecipitation reaction to obtain a quaternary precursor material; Step S2, mixing the quaternary precursor material obtained in step S1 with a sodium source and a compound containing M, and then sintering the mixture at a high temperature to obtain a positive electrode material for a sodium ion battery; Step S3, mixing the sodium ion battery positive electrode material obtained in step S2 with FeC2O4·H2O and (NH4)2HPO4, and then mixing them evenly by wet planetary ball milling. During the mixing process, FeC2O4·H2O and (NH4)2HPO4 react with the residual alkali on the surface of the sodium ion battery positive electrode material to generate NaFePO4, and then drying and grinding the mixture. Then, the obtained mixture is subjected to high temperature sintering and crushing to obtain the NaFePO4-coated sodium ion battery positive electrode material; Step S4, mixing the NaFePO4-coated sodium ion battery positive electrode material obtained in step S3 with acetylene black and mixing them evenly by wet planetary ball milling under an inert gas atmosphere. During the mixing process, the NaFePO4 coated on the surface of the sodium ion battery positive electrode material coated with NaFePO4 reacts with the residual alkali remaining on the surface to generate Na3FePO4CO3, thereby obtaining a sodium ion battery layered positive electrode material coated with NaFePO4 and Na3FePO4CO3; By consuming the residual alkali sodium carbonate on the surface of the sodium ion battery positive electrode material twice, the residual alkali on the surface of the sodium ion battery positive electrode material can be effectively reduced, and the stability of the material in the air can be effectively improved. The slurry stability of the sodium ion battery positive electrode material can be improved, and the gas production during the cycle of the sodium ion battery can be reduced; the coating layer formed by the sodium ion battery positive electrode material can isolate the electrolyte, reduce the direct contact between the positive electrode of the sodium ion battery and the electrolyte, and ensure the stability of the interface; the coating layer of the sodium ion battery positive electrode material is a sodium-containing compound, which can provide a part of the sodium source during the charge and discharge process of the sodium ion battery, and further improve the cycle stability of the sodium ion battery positive electrode material.

2. The method for preparing a layered positive electrode material for a sodium ion battery according to claim 1, characterized in that: In step S1, the soluble nickel salt is one or more of nickel sulfate, nickel chloride or nickel nitrate; the soluble ferrous salt is one or more of ferrous sulfate, ferrous chloride or ferrous nitrate; the soluble manganese salt is one or more of manganese sulfate, manganese chloride or manganese nitrate; the soluble copper salt is one or more of copper sulfate, copper chloride or copper nitrate; the ratio of the soluble nickel salt, the soluble ferrous salt, the soluble manganese salt and the soluble copper salt satisfies Na x Ni a Mn b Fe c Cu d M (1-a-b-c-d) O2 stoichiometric coefficient ratio.

3. The method for preparing a layered positive electrode material for a sodium ion battery according to claim 1, characterized in that: The sodium source in step S2 is one or more of sodium carbonate, sodium formate, sodium hydroxide, sodium acetate, sodium chloride or sodium fluoride, and the molar ratio of the sodium source to the quaternary precursor material satisfies Na / (Ni+Fe+Cu+Mn)=1:1; the compound containing M is an oxide or hydroxide containing M, and the feeding mass ratio of the compound containing M to the quaternary precursor material satisfies that the compound containing M is 0.08wt%~0.12wt% of the mass of the quaternary precursor material.

4. The method for preparing a layered positive electrode material for a sodium ion battery according to claim 1, characterized in that: The specific process of high temperature sintering in step S2 is: first heating the mixture to 400-600°C in air atmosphere and sintering for 4-8 hours, then heating it to 950-1050°C and sintering for 10-15 hours, and the heating rate is 2-5°C / min.

5. The method for preparing a layered positive electrode material for a sodium ion battery according to claim 1, characterized in that: The feeding ratio of the sodium ion battery positive electrode material to FeC2O4·H2O and (NH4)2HPO4 in step S3 satisfies that the molar ratio of the residual alkali content on the surface of the sodium ion battery positive electrode material to FeC2O4·H2O and (NH4)2HPO4 is 1:1~2:1~2.

6. The method for preparing a layered positive electrode material for a sodium ion battery according to claim 1, characterized in that: The specific process of the ball milling mixing in step S3 is: ball milling at a rotation speed of 500-600 rpm for 1-2 hours.

7. The method for preparing a layered positive electrode material for a sodium ion battery according to claim 1, characterized in that: The specific process of high temperature sintering in step S3 is: heating the mixture to 600-700° C. in an inert gas atmosphere and annealing for 8-10 hours, with a heating rate of 2-5° C. / min.

8. The method for preparing a layered positive electrode material for a sodium ion battery according to claim 1, characterized in that: The specific process of ball milling mixing in step S4 is: first, ball milling at a rotation speed of 500-600 rpm for 5-6 hours, during which the amount of acetylene black added is 20wt%-30wt% of the mass of the NaFePO4 coated sodium ion battery positive electrode material; and then ball milling at a rotation speed of 300-400 rpm for 3-4 hours, during which the amount of acetylene black added is 20wt%-30wt% of the mass of the NaFePO4 coated sodium ion battery positive electrode material.

Citation Information

Patent Citations

  • Method for reducing residual alkali content on surface of layered cathode material of sodium-ion battery and application

    CN111370664A

  • Sodium ion positive electrode material with low residual alkali content and preparation method thereof

    CN116613294A

  • Sodium-ion battery positive electrode material, preparation method thereof and sodium-ion battery

    CN117466346A

  • Positive electrode material, preparation method thereof and lithium ion battery

    CN116404109A

  • Sodium-ion battery layered oxide positive electrode material, preparation method thereof and sodium-ion battery

    CN117276551A